Exploring Media Influence On Contraceptive Use Among Indonesian Couples - Irawaty, Dian Kristiani; Gayatri, Maria (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
This paper evaluates whether mass media exposures, specifically television, radio, newspaper/magazine and internet, were effective tools for utilizing contraception among Indonesian couples. A sample of 8,925 Indonesian couples were selected based on the result of the 2017 Indonesia Demographic and Health Survey. Logistic regression models were used to predict recent media exposure (television, radio, newspaper/magazine and internet) to family planning messages and its association with contraceptive use among Indonesian couples. Internet exposure was found to be significant, and it had a strong effect on the likelihood that the Indonesian couples uses modern contraceptives. Region and number of living children were also found as significant effects on the modern contraceptive use. As such, internet as a promotion tool in campaigning family planning is more effective than television, radio, and newspaper/magazine) in improving contraceptive use among Indonesian couples.